Influence of Basic Health Care Provision Fund in improving primary Health Care in Kano state, a descriptive cross-sectional study - Zainab Auwalu Ibrahim; Kennedy Diema Konlan; Yoon Moonsoo; Paul Kwetishe; Jongsoo Ryu; Da Sol Ro; So Yoon Kim (BMC, 2023)
Abstract Background The Basic Health Care Provision Fund (BHCPF) is a direct financial investment that funds Primary Healthcare (PHC) to improve the quality of services. This study assessed the influence of the BHCPF in improving PHC services. Methods A descriptive cross-sectional study was conducted among PHC workers in 100 facilities randomly selected from the 484 designated PHCs for implementing the BHCPF project in Kano state. Using multiple sampling methods, 200 healthcare workers in PHC facilities were selected and assisted by trained data collectors to respond to the questionnaires. Chi-square analysis was used to show associated factors, while binary regression analysis was used to determine the relationship between factors influencing the BHCPF implementation in PHC. Result The findings showed healthcare workers had higher awareness (61.7%) and good utilization (57.1%) of BHCPF. Challenges of the BHCPF implementation were insufficiently skilled health professionals (85%), lack of data management capacity (52.6%), low community participation and awareness (52.0%), delay in releasing funds (60.7%), poor infrastructure (87.8%), and weak financial management and accountability system (58.2%). Healthcare professionals having a diploma were four times more likely to have the National Health Management Information System (NHMIS) in their facilities (AOR = 4.955, 95% CI = 1.120-21.036; P-value 0.035) than those without. Primary healthcare facilities were two times more likely to have the NHMIS (AOR = 2.549, 95% CI = 1.167-5.566: P-value 0. 019) than health post. Conclusion The factors that influenced PHC facilities to promote the implementation of BHCPF included: periodic evaluation of the facilities, availability of functional storage facilities, and improving the standard of care in PHC facilities. There is a need for retraining healthcare workers and creating more community awareness of the BHCPF.